(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Tuberculosis is a peculiar infectious disease because of the latent period between the infection and the appearance of the disease which may be prolonged for many weeks , months or years as it is in case of the secondary tuberculosis. Extra pulmonary tuberculosis gained new importance, because it represented a progressively greater proportion of new cases. Multiple extra pulmonary sites were reported rarely except for one anatomical site, which was reported frequently. A 20 yrs old boy was admitted at Dhaka National Medical Institute Hospital with pain at back, buttock and thigh with a swelling at the anterior aspect of upper part of left thigh. He was diagnosed as a case of tuberculosis of spine (D12 and L1) with psoas abscess with tuberculosis of hip joint (lt) and an enquiry and investigation found to have pulmonary TB as well. So this rare involvement of multiple tuberculosis is presented here. DOI: http://dx.doi.org/10.3329/jdnmch.v18i2.16026 J. Dhaka National Med. Coll. Hos. 2012; 18 (02): 61-63